Depth-driven patterns in lytic viral diversity, auxiliary metabolic gene content, and productivity in offshore oligotrophic waters - Tsiola, Anastasia; Michoud, Grégoire; Daffonchio, Daniele; Fodelianakis, Stilianos; Giannakourou, Antonia; Malliarakis, Dimitris; Pavlidou, Alexandra; Pitta, Elli; Psarra, Stella; Santi, Ioulia; Zeri, Christina; Pitta, Paraskevi (Frontiers in Microbiology, 2023)
Marine viruses regulate microbial population dynamics and biogeochemical cycling in the oceans. The ability of viruses to manipulate hosts' metabolism through the expression of viral auxiliary metabolic genes (AMGs) was recently highlighted, having important implications in energy production and flow in various aquatic environments. Up to now, the presence and diversity of viral AMGs is studied using -omics data, and rarely using quantitative measures of viral activity alongside. In the present study, four depth layers (5, 50, 75 and 1000 m) with discrete hydrographic features were sampled in the Eastern Mediterranean Sea; we studied lytic viral community composition and AMG content through metagenomics, and lytic production rates through the viral reduction approach in the ultra-oligotrophic Levantine basin where knowledge regarding viral actions is rather limited. This is a provisional file, not the final typeset article Our results demonstrate depth-dependent patterns in viral diversity and AMG content, related to differences in temperature, nutrients availability, and host bacterial productivity and abundance.Although lytic viral production rates were similar along the water column, the virus-to-bacteria ratio was higher and the particular set of AMGs was more diverse in the bathypelagic (1000 m) than the shallow epipelagic (5, 50 and 75 m) layers, revealing that the quantitative effect of viruses on their hosts may be the same along the water column through the intervention of different AMGs. In the resource-and energy-limited bathypelagic waters of the Eastern Mediterranean, the detected AMGs could divert hosts metabolism towards energy production, through a boost in gluconeogenesis, fattyacid and glycan biosynthesis and metabolism, and sulfur relay. Near the deep-chlorophyll maximum depth, an exceptionally high percentage of AMGs related to photosynthesis was noticed. Taken together our findings suggest that the roles of viruses in the deep sea might be even more important than previously thought as they seem to orchestrate energy acquisition and microbial community dynamics, and thus, biogeochemical turnover in the oceans.